Polarizing and Light Microscopic Analysis of Mineralized Components and Stromal Elements in Fibrous Ossifying Lesions - Rasika R Kulkarni; Sriranjani D Sarvade; Karen Boaz; Srikant N; Nandita KP; Amitha J Lewis (Journal of Clinical and Diagnostic Research, 2014)
Introduction: Fibro-osseous lesions, along with few reactive lesions of the jaws exhibit an overlapping histo-morphologic spectrum with respect to the nature of calcifications and stromal components. This causes difficulty in assessing the origin, pathogenesis and diagnosis of these lesions. Aim: The present study analyses the mineralized components, cellularity, stromal density and stromal composition (nature of collagen, presence of elastic and oxytalan fibres) in cases of ossifying fibroma (OF), fibrous dysplasia (FD) and peripheral ossifying fibroma (POF). Materials and Methods: The study included a histochemical evaluation of six cases each of FD, OF and POF. Five consecutive sections of each case were stained with hematoxylin and eosin, picrosirius red (to assess maturation of fibres in polarizing light), van Gieson (for area fraction and collagen density) and aldehyde fuchsin (for elastic and oxytalan fibres) respectively. Results: Significantly higher amounts of mature bone were seen in FD while cementicles having microlamellar pattern were predominant in OF and POF (p < 0.001). Area fraction, collagen density and immature stromal fibre content was higher in POF followed by FD and OF (p= 0.039). Oxytalan and elastic fibres were absent in FD. Conclusion: Higher cellularity of the stroma in OF was indicative of its neoplastic behaviour. Higher composition of oxytalan and elastic fibres in OF and POF supports their periodontal ligament origin. FD was distinct with more mature fibres in a lamellated bone and absence of oxytalan fibres.